Contextualizing Democratization and the Practice of Social Research - Pilotta, Joe (Sociologija. Mintis ir veiksmas, 2004)
Political communication is strictly distinguished from social and individual activities that are interest-laden and thus lack the autonomy to be political. The latter belongs solely to political societies that are democratic. Indeed, there must be a strict restriction of the use of political to a public domain in which every member of society participates in public debates and decisions. This participation is the continuous origination and maintenance of the political domain as a guarantee of human autonomy and equality.This equality suggests that the publicly appointed officials are bound by the democratic ethos to maintain such a public domain and thus are called on to communicate the public issues; any communication that is designed for effect, for rhetorical obfuscation, is interest-laden and hence designed to advance the motives of an individual or a group and not the concerns of the public. In various ways, such a communication, and those who in their expertise help in its design, adds to the legitimation crisis that leads finally to public cynicism.Political journalism, as part and parcel of the originating and maintaining of the political society, is designed to serve the public by providing information that is of public concern. This is not to say that gossip columns of social interest are to be excluded from mass media. Rather, the primary task is information – despite the tendency of the public officials and their experts to obfuscate and mislead. One could in fact argue that political journalism and communication is, by now, the primary instrument of continuing the origination and maintenance of political (i.e., democratic) society (Mickunas, Pilotta 1999).
Keywords: democracy; knowledge society; Alfred Schütz; social research; life world; dialogue; well-informed citizen